Z Sambora do Zielonej Góry. Antoniny Żulik album rodzinny - Grabias-Banaszewska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text is focused on Antonina Żulik`s family archive. The author evokes the figure of the forgotten Pioneer of Zielona Góra, who came to the city from Sambor in the borderlands. From the album emerges a rudimentary history of the Galician intelligentsia family, which the author enriches with a rich album of photographs and family documents. The text is regionalistic.
Keywords: rodzina; regionalizm; przesiedlenia; fotografia; źródło historyczne; dziedzictwo; family; regionalism; resettlements; photography; historical sources research; heritage